Charles Taylor and Liberia ambition and atrocity in Africa?s Lone Star State - Waugh, Colin M. (London Zed Books, 2011)
Campaigner, insurgent, arms dealer, warlord, commodity trafficker, elected president, international fugitive, and finally prisoner, Charles Taylor sought to lead his native Liberia to change but instead destroyed it in a frenzy of violence, greed, and uncontrolled personal ambition. In the process, he threw much of Liberia's neighboring region into turmoil for over a decade, finally facing judgment in The Hague for his role in the Sierra Leone conflict. In this remarkable and eye-opening book, Colin Waugh examines both the life of Taylor himself, as well as the sometimes idealistic but often self-interested efforts of the international community to first save Liberia and the region from disaster, then, having failed to do so, to bring to justice the man it deems most to blame for the turmoil.
Includes bibliographical references (p. [360]-363)
Keywords: aylor, Charles Ghankay. Presidents-Liberia-Biography. Liberia-History-Civil War, 1989-1996. Liberia-History-Civil War, 1999-2003. Liberia-Politics and government-1980